Kinematicni parametri položaja za izmet in izmeta pri vrhunskih metalkah kopja - Panoutsakopoulos, V.; Kollias, A. I. (Kinesiologia Slovenica, 2013)
The introduction of the new-rules javelin for female athletes in 1999 was thought to be a cause of increased demand for excellence in the throwing technique and that a greater demand for biomechanical analysis was stressed. The purpose of the study was to investigate the kinematical parameters of the delivery phase and the release parameters of contemporary top female javelin throwers in order to support the above mentioned suggestion. Twenty-six throws performed during competitions by 16 right-handed top athletes (age: 28.5 years ± 4.3; body height: 1.75 m ± 0.05; body mass: 73.8 kg ± 6.3; average ± standard deviation, respectively) were recorded with a digital video camera (sampling frequency: 50fps). The delivery and release phases were examined with a 2D-DLT analysis method. The relationship of the extracted spatiotemporal, kinematical and release parameters with the official throwing distance was examined with a two-tailed Pearson correlation. The results indicated that the official distance (59.22 m ± 4.42) was strongly correlated (r = .909).